Pola Perilaku Konsumsi Islami Mahasiswa Muslim Fakultas Ekonomi dan Bisnis Universitas Airlangga Ditinjau Dari TIngkat Religiusitas - Yolanda Hani Putriani; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims to know how Islamic Pattern Behavior Consumption of Students Faculty Economics and Business University Airlangga in in Choosing Halal Food and Thayyib reviewed by level of religiosity. The method that used is qualitative approach with a case study strategy. Data was collected by interviews and direct observation of the object research. The analysis technique that used is descriptive qualitative analysis that is narrating the results of interviews and direct observation. Based on the results of the study concluded that the Faculty of Economics and Business University Press Islamic behavior patterns of consumption good and there is no difference between students of each program of study. Suggestions for further research should deepen the Islamic consumption behavior of various faculties at the University of Airlangga.